The effect of oxygen saturation targeting on retinal blood vessel growth using retinal image data from the BOOST-II UK Trial - Moreton, R; Fleck, B; Fielder, A; Williams, C; Butler, L; Wilson, C; Cocker, K; Juszczak, E; King, A; Stenson, B; Brocklehurst, P (Nature Publishing Group, 2016)
Purpose: Retinopathy of prematurity (ROP) is a disorder of developing retinal blood vessels in preterm infants. The purpose of this nested study was to investigate the effects of higher (91-95%) and lower (85-89%) oxygen saturation (SpO2) targeting on retinal blood vessel growth in preterm infants. Methods: Retinal blood vessel growth in the higher (91-95%) and lower (85-89%) oxygen saturation (SpO2) targeting groups was compared. Suitable RetCam (Clarity, Pleasanton, CA, USA) images collected in the BOOST-II UK trial were used. The distances between the centre of the optic disc and the ROP ridge in the temporal and nasal retina were measured in pixel units. Results: Images from 38 infants were studied, 20 from the higher SpO2 target group and 18 from the lower SpO2 target group. On average, temporal blood vessels extended further from the optic disc than nasal blood vessels, mean (standard deviation (SD)) 463.39 (55.05) pixels compared with 360.13 (44.47) pixels, respectively, P<0.0001. Temporal blood vessels extended less far from the optic disc in the higher SpO2 target group than in the lower SpO2 target group: mean (SD) 449.83 (56.16) pixels compared with 480.02 (49.94), respectively, P=0.055. Nasal retinal blood vessel measurements were broadly similar in the higher and lower SpO2 target groups; mean (SD) 353.96 (41.95) compared with 370.00 (48.82) pixels, respectively, P=0.38. Conclusions: Relatively high oxygen saturation targeting (91-95%) was associated with a trend (P=0.055) towards reduced retinal blood vessel growth in this study of preterm infants.